Playing hide and seek underwater: Evidence of orca (Orcinus orca) presence in offshore Icelandic waters through acoustic analysis - Giulia Bellon 1992- (2023)
Understanding orca (Orcinus orca) movement patterns in relation to prey is important for conservation management. In the North Atlantic, orcas are known to have a close relationship with herring, being regularly sighted feeding in coastal herring grounds. However, the distribution of orcas in offshore waters is less monitored and therefore poorly understood. This study investigated the acoustic presence of orcas across four regions of Iceland to gain knowledge on their seasonal distribution and population origin based on their calls. Six passive acoustic devices were deployed between 2018 and 2022, with four of which in offshore waters. Acoustic recordings were analysed to identify and categorise orca pulsed calls and these calls were compared with published catalogues from Iceland and Norway. The comprehensive comparison, based on 3,876 high-quality calls identified, revealed 760 matches to 29 call types attributed to the Icelandic orca population, providing evidence of orca presence at all monitoring sites. Most orca sounds were detected in the East and Northeast of Iceland during the summer months, suggesting individuals were possibly feeding on the Norwegian spring-spawning herring, which in recent years has returned to this area during the summer months. Herding calls were detected in the South during the winter months, suggesting orcas feed in the region throughout the year and not just in summer, as previously thought. Three calls identified in East Iceland in April were matched to the Norwegian call type catalogue, suggesting that Icelandic waters are visited by orcas from other populations. This study extends the known orca habitat in Iceland to all offshore regions monitored. While most individuals are likely to be a part of the Icelandic population, the detection of Norwegian call types suggests connectivity between Northeast Atlantic orca populations that requires further study. Að skilja hreyfimynstur háhyrninga (Orcinus orca) í tengslum við bráð er mikilvægt fyrir nátturuvernd. Í ...